The relationship between upper airway parameters and COVID-19 symptom severity in adolescents - Tianjing Du; Juan Wang; Peter Mei; Dongning Li; Jiamin Zhao; Jianglin Zhou; Jun Wang; Yifei Xu; Kun Qi (Frontiers Media S.A., 2024)
BackgroundCOVID-19 is a respiratory disease, and its symptoms may be affected by the upper airways of adolescents.ObjectiveTo investigate the effect of parameters of adolescents' upper airways on COVID-19 symptom severity.MethodsThis retrospective study was performed from January to March 2022 at the Hospital of Stomatology, Xi'an Jiaotong University, Xi'an, China. The inclusion criteria were patients who started orthodontic treatment for the first time, who experienced initial onset of laboratory-confirmed COVID-19, and who received two intramuscular doses of the SARS-CoV-2 vaccine. Participants' COVID-19 symptom severity was recorded by a questionnaire including seven different dimensions. The three-dimensional parameters of the upper airway were obtained by cone beam computed tomography (CBCT) and measured by Dolphin Imaging software by blinded orthodontic investigators. The correlation between COVID-19 symptom severity and three-dimensional upper airway parameters was analyzed.Results64 males (46.4%) and 74 females (53.6%) were included in the study, with the median age of 9.5 years. The severity score of dimension 3 (headache, muscle pain, fatigue, shortness of breath, diarrhea and smell affects) showed a linear relationship with age. Spearman's rank correlation showed that the severity score of dimension 1 (nasal symptoms) was negatively correlated with nasal volume (r = −0.325). The severity score of dimension 6 was negatively correlated with the height of the nasopharynx (r = −0.325) and positively correlated with the horizontal-to-vertical ratio of the oropharynx (r = 0.385).Conclusions and relevanceThe COVID-19 symptom severity was aggravated with the increase of age. Nasal and throat pain and dry mouth was negatively correlated with nasal volume and nasopharyngeal height. The COVID-19 symptom severity among individuals is relavant to age and upper airway.